Solitary fibrous tumor of the kidney with focus on clinical and pathobiological aspects - Kuroda, Naoto; Ohe, Chisato; Sakaida, Noriko; Uemura, Yoshiko; Inoue, Keiji; Nagashima, Yoji; Hes, Ondrej; Michal, Michal (International journal of clinical and experimental pathology, 2014)
Renal solitary fibrous tumor (SFT) is a rare, and a large scale study on this topic is lacking to date. In this article, we summarize the previously reported cases. The symptoms and signs resemble those of renal cell carcinoma, including hematuria, flank/abdominal/lumbar pain and palpable abdominal mass. Grossly, the tumor demonstrates a well-circumscribed solid mass. Microscopically, the tumor consists of fusiform or ovoid spindle cells and a various amounts of collagen bundles with patternless, storiform, or fascicular arrangements with an occasional hemangiopericytomatous pattern. Immunohistochemically, CD34, CD99 and bcl-2 are often detected. Ultrastructurally, tumor cells contain irregular nuclei, prominent Golgi apparatus, branching rough endoplasmic reticulum, variable numbers of mitochondria. Surgical resection is considered to be the gold standard therapy. Most of renal SFT are benign, but cases of approximately 10 to 15% behave in an aggressive fashion. All patients need to be on long-term follow-up because clinical behavior is rather unpredictable. As the molecular genetic study of renal SFTs is lacking, a large scale study will be desirable in the future.
Keywords: CD34; nádory ledvin; Solitary Fibrous Tumors; Kidney Neoplasms; solitární fibrózní tumory; Solitary fibrous tumor; lidé; kidney; Humans; STAT6